Implementation of the Use of the Tilawati Application to Support Tahsin Teaching Staff for Effective Learning at State Islamic Institute Curup - Pingki Utami; Idi Warsah; Dewi Purnama Sari (CV Media Inti Teknologi, 2023)
The Tilawati app allows teachers to monitor individual students' progress more efficiently. Student progress data, including memorization and comprehension levels, is easily accessible, allowing teachers to provide more targeted guidance. This study aims to evaluate the impact of the implementation of the Tilawati application as a tahsin learning aid at the State Islamic Institute (IAIN) Curup. The focus of this research is how the Tilawati application can be used to support tahsin teaching staff in improving learning effectiveness. The research method used is classroom action research with a qualitative approach. The results showed that the use of the Tilawati application had a positive impact on tahsin learning at IAIN Curup. This research makes an important contribution to the understanding of how the use of the Tilawati application can improve the effectiveness of tahsin learning at IAIN Curup. Some of the key findings include: The Tilawati app provides an interactive and engaging learning experience for students. Therefore, from the results of the study, it can be concluded that the implementation of the Tilawati application contributes positively to the overall quality of tahsin learning. Students are more motivated, and the learning process becomes more adaptive according to individual needs.